Non-inhibitory effects of the potent antioxidant C-phycocyanin from Plectonema sp. on the in vitro glycation reaction - Husain Arbab; Alouffi Sultan; Khanam Afreen; Akasha Rihab; Khan Saif; Khan Mahvish; Farooqui Alvina; Ahmad Saheem (Romanian Journal of Laboratory Medicine, 2022)
When glucose and Amadori products are auto-oxidized, glycation occurs, resulting in the formation of early (Amadori) and late advanced glycation end products (AGEs), as well as free radicals. Glycation and an increase in free radical activity induce diabetic complications. Antioxidant and antiglycation compounds may aid in the prevention of oxidation and glycation. The goal of this study was to assess the antiglycation and antioxidant capacity of C-phycocyanin (C-PC) derived from Plectonema sp. The DPPH (1, 1-diphenyl-2-picrylhydrazyl), nitric oxide, hydroxyl radical scavenging activities and ferric ions reducing antioxidant power (FRAP) assays were used to assess antioxidant activity, while an in vitro bovine serum albumin-methyl glyoxal glycation (BSA-MG) model was used to assess glycation inhibitory potential. Glycation inhibition was measured using a variety of spectroscopic and biochemical parameters, including UV-visible & fluorescence spectroscopy, ketoamine, carbonyl and hydroxymethyl furfural content, as well as free lysine & free arginine estimations. In vitro, C-PC exhibited dose-dependent potent antioxidant activity, but lacked significant antiglycation potential. As a result, it is recommended that further studies be conducted to evaluate the antiglycation potential of C-PC.